Cycling strength vs. gym strength for endurance cyclists - Halme, S.; Malmstedt, L.; Schumann, M.; Cheung, S.; Ahtiainen, J. (19th International Symposium "Modern Science and Practice for Strength and Endurance Training" October 10-12, 2018, 2020)
Combined strength and endurance training can develop strength and endurance performance of endurance athletes just as well or better than endurance training alone. Also short 30 seconds power cycling intervals have shown to increase long-term endurance performance. However, efficacy of short high resistance bike intervals (< 15 sec) that demands high neuromuscular capacity, have not been studied. The aim of this study was to investigate and compare the effects of bike strength intervals and gym strength exercises on cyclists` performance.